2020
DOI: 10.1002/jbmr.4261
|View full text |Cite
|
Sign up to set email alerts
|

High Cardiovascular Risk in Older Men with Poor Bone Microarchitecture—The Prospective STRAMBO Study

Abstract: Data on the association between bone microarchitecture and cardiovascular disease (CVD) in men are scarce. We studied the link of bone microarchitecture and areal bone mineral density (aBMD) with the risk of major adverse coronary event (MACE) in a cohort of men aged 60 to 87 years followed prospectively for 8 years. At baseline, aBMD was measured using a Hologic Discovery‐A device. Bone microarchitecture was assessed at distal radius and tibia by high‐resolution peripheral quantitative computed tomography (Xt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Several studies showed that preserved cortical bone status and strength are associated with a lower risk of major adverse coronary events [ 50 ]. Interestingly, increased levels of sclerostin were found both in serum and bone specimens of patients with type 2 diabetes [ 51 , 52 ], post-menopausal women compared to pre-menopausal ones [ 22 , 53 ], immobilized postmenopausal women with bone resorption markers elevation [ 54 ] and postmenopausal women with osteoporosis compared to postmenopausal women without osteoporosis, even if no correlation was seen with BMD [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that preserved cortical bone status and strength are associated with a lower risk of major adverse coronary events [ 50 ]. Interestingly, increased levels of sclerostin were found both in serum and bone specimens of patients with type 2 diabetes [ 51 , 52 ], post-menopausal women compared to pre-menopausal ones [ 22 , 53 ], immobilized postmenopausal women with bone resorption markers elevation [ 54 ] and postmenopausal women with osteoporosis compared to postmenopausal women without osteoporosis, even if no correlation was seen with BMD [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following informed consent, participants underwent medical exams, with no exclusion criteria applied. Among those included in the original cohort, 825 men older than 60 years were followed up prospectively ( 14 ). Of the 755 participants within the study, 112 reported cardiovascular events prior to recruitment, namely acute myocardial infarction (AMI) and ischemic heart disease (IHD).…”
Section: Methodsmentioning
confidence: 99%
“…Serum osteoprotegerin was measured by ELISA (Biomedica Medizinprodukte GmbH & Co Kg, Vienna, Austria) as described previously ( 16 ). Serum parathyroid hormone was measured using a human-specific two-site immunochemiluminescence assay (ELECSYS; Roche) as described previously ( 14 ). Serum 25-hydroxycholecalciferol was measured with RIA (DiaSorin, Stillwater, MN) after acetonitrile extraction ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 8,9 ) It is generally considered that bone condition as evaluated by BMD in CKD patients may have much greater impacts on major health outcomes, such as vascular calcification and other cardiovascular diseases, compared with the general population. ( 7,10,11 ) In previous studies, low BMD measured by whole‐body DXA was associated with increased risk of fractures and cardiovascular disease mortality in patients with ESRD and/or hemodialysis. ( 12‐15 ) Furthermore, previous cohort study suggested that cortical bone such as arm tended to be more strongly associated with mortality than trabecular bone in CKD patients; however, other studies indicated that BMD at hip and spine may be the optimal sites to reflect bone loss and predict survival in ESRD or hemodialysis patients.…”
Section: Introductionmentioning
confidence: 96%